Student’s Perception on The Use of Code-Crossing in The Online Classroom Interaction (Zoom Cloud Meetings) - Murni Mahmud; Abdul Halim; Indrayani Simpuruh (Universitas Negeri Makassar, 2023)
Abstract. This research aims to explore the phenomena of code-crossing in the teaching of English as a foreign language. It cannot be denied that in the classroom interaction, there are many aspects influencing the success of the communication between the lecturers/teachers and the students. One of the interesting aspects is the influence of social status differences which lead to the occurrence of code-crossing in the class. For that purpose, the study in this paper is directed to explore the perspectives on the use of code-crossing in the class, focusing on the online classroom interactions via Zoom Cloud Meetings. This research applied a qualitative research design taking one English class and their students at Universitas Negeri Makassar as the subject. The data of this paper were collected by employing a semi-structured interview by focusing on the students taken purposively among 40 students of the English class. The interview was also conducted through the online communication (WhatsApp chats). The data were analyzed descriptively by using qualitative model analysis (Miles, et al 2014). The result of the research shows that from the student’s point of view, most students did code-crossing in the online classes because they wanted to respect and speak formally to the older people (lecturers and seniors). In addition, for some students interviewed by the researchers, they thought that the use of code-crossing could show politeness. Findings from this study are worthy of reading for English language teaching practitioners in their effort to create effective classroom interaction both in the face-to-face interaction and online interaction. Keywords: Code-Crossing; Language And Power; Social Status; Students’ Perception; Online Classes